2008
DOI: 10.1111/j.1600-6143.2008.02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma in Organ Transplant Recipients: Clinicopathological Features and Outcome in 100 Cases

Abstract: Organ transplant recipients have a higher incidence of melanoma compared to the general population but the prognosis of this potentially fatal skin cancer in this group of patients has not yet been established. To address this, we undertook a multicenter retrospective analysis to assess outcome for 100 melanomas (91 posttransplant and 9 pretransplant) in 95 individuals. Data were collected in 14 specialist transplant dermatology clinics across Europe belonging to the Skin Care in Organ Transplant Patients, Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
76
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(89 citation statements)
references
References 52 publications
(65 reference statements)
12
76
0
1
Order By: Relevance
“…43 Recent studies of organ transplant despite a history of melanoma have not found an increased risk of worse outcomes in these cases. 5,6,45 In essence, although melanoma is a serious malignancy, these studies raise the question of whether melanoma should be an exclusion criterion for a lifesaving organ transplant. To date, no conclusive evidence suggests that patients who have a diagnosis of melanoma would fare worse after receiving an organ transplant.…”
Section: Article Highlightsmentioning
confidence: 99%
See 3 more Smart Citations
“…43 Recent studies of organ transplant despite a history of melanoma have not found an increased risk of worse outcomes in these cases. 5,6,45 In essence, although melanoma is a serious malignancy, these studies raise the question of whether melanoma should be an exclusion criterion for a lifesaving organ transplant. To date, no conclusive evidence suggests that patients who have a diagnosis of melanoma would fare worse after receiving an organ transplant.…”
Section: Article Highlightsmentioning
confidence: 99%
“…Some studies have documented findings about survival, metastatic potential, and other aspects of the clinical course. 6,25,47 De novo melanomas tend to develop 3 years posttransplant or later, 40 with reports ranging from 14 to 236 months. 29 The mean time for melanoma development in the OTR population is 61 months posttransplant, 44 with some studies documenting a range of 40 to 132 months.…”
Section: Clinical Course Of Melanoma In Solid Organ Transplant Recipimentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have reported no deaths due to melanoma in cases of malignant melanoma in situ or thin superficial spreading melanoma in the organ transplant recipients. 29,34,44,52 In a recent European multicenter retrospective study of 100 melanomas (91 occurred posttransplant) in OTRs, Matin et al 6 found the overall 2-, 5-, and 10-year survivals to be 77%, 54.2%, and 40.6%, respectively, in OTRs, compared with 95.6%, 82.1%, and 75.2% (2-, 5-, and 10-year survivals, respectively; Pϭ.0019) for age-, sex-, tumor thickness-, and ulceration statusmatched control subjects from the American Joint Committee on Cancer melanoma database. However, when broken down by thickness, outcomes were not significantly different among the T1 and T2 (Յ2 mm) posttransplant melanoma patients compared with the control subjects of the American Joint Committee on Cancer.…”
Section: Clinical Course Of Melanoma In Solid Organ Transplant Recipimentioning
confidence: 99%